The Determinants of Bank Profitability Empirical Evidence from Vietnamese Commercial Banks in The Periods Of 2013 To 2018 - Nguyen, Dan Ngoc Minh; Vu, Anh (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
This research concentrates on the determinants of the profitability of the Vietnamese Commercial Banks. Both internal and external variables regarding the profitability of commercial bank sector will be focused in the analysis. Data over the period of 2013 to 2018 for 29 Vietnamese Commercial Banks[i] is obtained from via Stock Exchange or media. Fixed effect panel model are used to analyze the determinants of the profitability. By using this, we ensure for the effectiveness of the test result in terms of hypothesis along with size in order to get consistent results. The research is based on the scientific approach of quantitative methods to solve the problems posed, practical and effective service for the completion of the research purpose. The secondary data collected from the worldbank.org, vietdata.vn and annual reports (financial statement, balance sheet, etc.) of Vietnamese commercial banks in the 2013-2018 period to create asymmetric data tables will be processed on STATA software.